Confirmation of a Protein–Protein Interaction in the Pantothenate Biosynthetic Pathway by Using Sortase‐Mediated Labelling. (1st March 2016) - Morrison, Philip M.; Balmforth, Matthew R.; Ness, Samuel W.; Williamson, Daniel J.; Rugen, Michael D.; Turnbull, W. Bruce; Webb, Michael E.
Abstract: High‐throughput studies have been widely used to identify protein–protein interactions; however, few of these candidate interactions have been confirmed in vitro. We have used a combination of isothermal titration calorimetry and fluorescence anisotropy to screen candidate interactions within the pantothenate biosynthetic pathway. In particular, we observed no interaction between the next enzyme in the pathway, pantothenate synthetase (PS), and aspartate decarboxylase, but did observe an interaction between PS and the putative Nudix hydrolase, YfcD. Confirmation of the interaction by fluorescence anisotropy was dependent upon labelling an adventitiously formed glycine on the protein N‐terminal affinity purification tag by using Sortase. Subsequent formation of the protein–protein complex led to apparent restriction of the dynamics of this tag, thus suggesting that this approach could be generally applied to a subset of other protein–protein interaction complexes. Abstract : PS, there's a second interaction : A combination of calorimetry and sortase‐mediated fluorescence labelling has been used to confirm the existence of a second protein–protein interaction—between pantothenate synthetase (PS) and a putative hydrolase—in bacterial pantothenate biosynthesis.